PENGEMBANGAN KAPASITAS INSPEKTORAT DALAM MENINGKATKAN KINERJA PENGAWASAN DI KOTA TUAL - Rakhmat .; Leopold P. Tethool (Jurnal Paradigma (JP), 2017)
In order to improve supervision performance process in the local area, Inspectorate is currently faced with the proportional and accountable mechanisms problems and the development of inadequate capacity.  This qualitative research is using a case study approach with asserting participant involvement of informants drawn from the structural position, functional, technical and administrative staff Inspectorate Tual scope. The results show that: (1) institutional development process based on three aspects of development, namely the development of human resources, institutional development and organizational aspects, (2) Various factors have determined the quality of the performance results of the implementation of institutional development in the Inspectorate office of Tual City, including the human factor is still relatively weak, the issue and aspects of coordination between and across agencies, and problems of cooperation and leadership support. The study was expected to provide recommendations for performance improvement in Tual control through institutional development efforts Tual Inspectorate Office.